1991
DOI: 10.1128/aem.57.4.1213-1217.1991
|View full text |Cite
|
Sign up to set email alerts
|

Influence of phenols on growth and membrane permeability of free and immobilized Escherichia coli

Abstract: The inhibition of the exponential growth of Escherichia coli K-12 by different phenolic compounds was examined. Cells entrapped in calcium alginate showed a greater tolerance than cells grown in suspension. The extent of inhibition of growth of the immobilized cells depended on the period of growth in the gel matrix. After the addition of bacteriostatic concentrations of phenol or 4-chlorophenol, a dose-dependent efflux of metabolites such as ATP and of K+ ions was elicited. Provided that glucose was supplied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(84 citation statements)
references
References 19 publications
5
75
0
1
Order By: Relevance
“…Leakage of K + is an indicator of impaired cell envelope integrity because it is accumulated in the cytoplasm of methanogens in exchange for Na + (Sprott and Jarrell 1981). Cellular ATP efflux was investigated as it is known to coincide with the leakage of K + and the dissipation of cell membrane potential after exposure to antimicrobials in bacteria (Heipieper et al 1991;Aronsson et al 2005;Higgins et al 2005). For the first time, we used this functional indicator in Archaea and showed that it can indeed be applied as another sign of a destroyed cell envelope as it coincided with K + leakage.…”
Section: General Effects Of C 12 and C 14 On Methanobrevibacter Ruminmentioning
confidence: 99%
“…Leakage of K + is an indicator of impaired cell envelope integrity because it is accumulated in the cytoplasm of methanogens in exchange for Na + (Sprott and Jarrell 1981). Cellular ATP efflux was investigated as it is known to coincide with the leakage of K + and the dissipation of cell membrane potential after exposure to antimicrobials in bacteria (Heipieper et al 1991;Aronsson et al 2005;Higgins et al 2005). For the first time, we used this functional indicator in Archaea and showed that it can indeed be applied as another sign of a destroyed cell envelope as it coincided with K + leakage.…”
Section: General Effects Of C 12 and C 14 On Methanobrevibacter Ruminmentioning
confidence: 99%
“…In mid-exponential growth phase, aliquots (10 ml) of cultures were harvested and centrifuged. The K content of the cells was determined by the method of Heipieper et al [15]. The cell pellet was disrupted by boiling in 5 ml of 5% trichloroacetic acid, and debris removed by centrifugation.…”
Section: Determination Of Potassium Retention and E¥uxmentioning
confidence: 99%
“…Published by Elsevier Science B.V. All rights reserved. PII: S 0 3 7 8 -1 0 9 7 ( 0 1 ) 0 0 4 3 6 -0 pieper et al [15] found that when E. coli K-12 was subjected to increasing phenol concentration the K content of the cells decreased signi¢cantly. This suggested that phenol had compromised the cell membrane, leading to the loss of metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…90,91 As has also been reported for other hydrophobic, membrane accumulating species, such interactions lead to membrane swelling and increased fluidity, 92,93 ultimately resulting in membrane leakage, 94 modified membrane protein activity, 95 and dissipation of the transmembrane proton gradient which in turn impacts cellular energy status, intracellular pH, and chemical homeostasis. [96][97][98][99][100] Production of styrene in E. coli, for example, was found to induce membrane damage and leakage (contrastingly, exogenous addition of styrene triggered little change in membrane integrity). 101 In addition to this common and general mechanism, inhibition imposed by aromatics can also further depend upon structural and functional group diversity.…”
Section: Enhancing Tolerance Towards Aromatic Biochemicalsmentioning
confidence: 99%